Critical Analysis on the Women Employees Work-life Balance during Covid-19 Pandemic in the Airline Industry in Sultanate of Oman. - AlRaiisi, Ghalia (Advances in Social Sciences Research Journal, 2021)
It has always been a difficult challenge to achieve a satisfactory work-life balance for everyone working in different industries. Still, it is a lot difficult to maintain, especially for women. The purpose of this paper is to find out the problems encountered by women employees of the Airline Industry in Sultanate of Oman to keep up the work-life balance during pandemic while upholding their physical and mental health status at best. This study intends to perceive how the women employees of the Airline Industry in the Sultanate of Oman maintained the work from home because it is not easy to do the house chores and office work at the same time (Moosa, 2017). The existing problems because of the pandemic pushed women employees' mental and physical health at the edge. However, pandemics also open a new gate for women employees to go beyond their limitations and to fight and compete in such situations. The paper has also covered some restrictions about the study with a detailed discussion on the background, scope, and significance of deconstruction. The ongoing research is also about seeking out some solutions for women employees to balance work and life. Further, the paper also includes a few bits of advice for the Airline Industry in the Sultanate of Oman that what steps it should take to make life easy for women employees to attain work-life balance.